Systematic review and meta-analysis of late diagnosis of Autism Spectrum Disorder (ASD) in women - Herman Marques, Nicole Sofia; Quint, Fernanda Cristine; Martins da Silveira, Jocelaine; Oliveira de Vasconcelos, Fábio Augusto; Fernandes de Souza, Mateus; Taconeli, Cesar Augusto; Padilha da Silva, José Luiz; Shimakura, Silvia (Brazilian Journal of Biometrics, 2025)
This article investigates the late diagnosis of Autism Spectrum Disorder (ASD) in women, identifies factors contributing to underdiagnosis and estimates the average age of diagnosis for women diagnosed after the age of 15. Following systematic review and meta-analysis guidelines, the study qualitatively analyzed literature from seven databases and assessed the quality of the studies. A random-effects meta-analysis was used to calculate the average age of diagnosis. Out of 102 studies reviewed, 17 involving 472 women were selected for quantitative analysis. The "Extreme Male Brain," "Female Phenotype," and "Protective Female Effect" theories were identified as factors for underdiagnosis, with an average diagnosis age of 28.24 years and high variability (I² = 99%). The study highlights the need for improved diagnostic strategies and psychological support for women with late ASD diagnosis.